PARENTING DAN SEMINAR PENDIDIKAN KARAKTER SEBAGAI UPAYA PEMBENTUKAN KARAKTER SISWA SMP & SMA SEKOLAH ANGKASA LANUD SOEWONDO MEDAN - Maria, Elvie; Manalu, Brilliant Handyman; Hartono, Hartono; Nadapdap, Kristanty M. N.; Sudarso, Andriasan; Pasaribu, Dompak (Universitas Methodist Indonesia, 2023)
The acts of crime and delinquency among children and teenagers continue to increase, such as robbering, mugging, stealing, rape, brawls, bullying and even murder, as well as other acts of violence, as well as their mental health conditions becoming increasingly worrying, which is marked by an increase in suicide attempts and suicides. Therefore, there needs to be cooperation from both of the government and society, by looking at the psychological side of the individual perpetrator, the parenting style of the family, community and society at large so that similar acts do not continue to increase. Observing this phenomenon as a form of concern and seriousness in preventing similar actions, Yasarini (Ardhya Garini Foundation), known as Sekolah Angkasa Lanud Soewondo, collaborated with the Developer Company PT. Taman Malibu Indah and Writers, located in the Mustang Hall Jalan Komodor Muda Adi Sucipto Medan, held activities in the form of Parenting for parents of students and Lectures for Middle and High School students at Sekolah Angkasa Lanud Soewondo, by providing an understanding of character values related to God, by yourself, with each other and the environment. The aim of the activity are the parents and students to know the importance of having good and strong character which can lead students had to become human resources advantage in welcoming Indonesia Gold in 2045.